Age-Related Variations in Tumor Suppressor Genes and Hormone Receptor Expression in Breast Cancer Patients - Mohammedsalih , Mehri Mirhaj; Kakey , Ismail Salih Ibrahim (AL-Kindy College Medical Journal, 2025)
Background: This study investigated the immunohistochemical expression of hormone receptors (ER, PR, HER2, Ki-67) and tumor suppressor genes (PTEN, p53) in women with breast cancer from Erbil, Iraq, focusing on how these expressions relate to patient age.Subjects and Methods: Between April and October 2024, 120 female breast cancer patients took part in a cross-sectional study. Immunohistochemical analysis was performed to evaluate the expression of PTEN, p53, ER, PR, HER2, and Ki-67.Results: Age was significantly positively correlated with PTEN loss, which was shown in 86.7% of patients (p < 0.001). Additionally, there was a positive connection between age and the expression of ER and PR (χ² = 26.67 for ER and 15.59 for PR). There was less correlation between HER2 positive and age. 34.2% of tumors had P53 expressions, which were unrelated to age. All tumors were discovered to contain Ki-67, indicating that active proliferation is taking place. Furthermore, there were notable variations in the expression levels of PTEN, P53, ER, PR, Ki-67, and HER2 according to tumor grade, which is a sign of the biology and aggressiveness of the tumor.Conclusions: While P53 expression does not significantly change with patient age, PTEN, ER, PR, and HER2 expression do. Ki-67 universal expression indicates that tumor proliferation is high in this population. Tumor aggressiveness and biology variations are highlighted by the variance in important biomarker expression by tumor grade.